Optimalisasi keaktifan belajar melalui model pembelajaran SSCS: Eksperimentasi di SMA - Fatkurohmah, Diana; Gani, A; Wahyudi, Didik (Program Studi Magister Pendidikan Agama Islam, 2026)
Students’ learning activeness is one of the important indicators of the success of the learning process. However, the results of a preliminary study conducted at SMA Negeri 1 Jayapura, Ogan Komering Ulu Timur, indicate that the level of students’ learning activeness is still not optimal, particularly in the aspect of independently seeking information. This condition is caused by the learning process that still tends to be teacher-centered, resulting in limited student involvement in learning activities. This study aims to determine the effectiveness of the Search, Solve, Create, and Share (SSCS) learning model in improving students’ learning activeness in the subject of Islamic Religious Education. The study employed a quantitative approach using a quasi-experimental method with a post-test-only control group design. The sample consisted of 57 students divided into an experimental class and a control class. Data were collected through observation and a learning activeness questionnaire. The results of the instrument testing indicate that most of the statement items were valid, with a Cronbach’s Alpha reliability coefficient of 0.738, indicating a good level of reliability. The normality test using the Shapiro–Wilk test showed significance values of 0.126 for the experimental class and 0.776 for the control class (p > 0.05), indicating that the data were normally distributed, while the homogeneity test using Levene’s Test obtained a significance value of 0.061 (p > 0.05), indicating that the variances of the two groups were homogeneous. Furthermore, the results of the independent sample t-test showed a significance value of 0.000 < 0.05 with a t value of 7.406. Therefore, it can be concluded that the SSCS learning model is effective in improving students’ learning activeness in Islamic Religious Education learning at the senior high school level. Abstrak Keaktifan belajar peserta didik merupakan indikator penting dalam keberhasilan pembelajaran, namun di SMA Negeri 1 Jayapura Ogan Komering Ulu Timur masih belum optimal, terutama pada aspek mencari informasi secara mandiri. Hal ini disebabkan oleh proses pembelajaran yang masih cenderung berpusat pada guru sehingga keterlibatan siswa dalam kegiatan belajar menjadi terbatas. Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran Search, Solve, Create, and Share (SSCS) terhadap keaktifan belajar peserta didik pada mata pelajaran Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen semu (quasi-experimental design) melalui desain post-test only control group. Sampel penelitian berjumlah 57 peserta didik yang terdiri dari kelas eksperimen dan kelas kontrol. Teknik pengumpulan data dilakukan melalui angket keaktifan belajar. Hasil uji instrumen menunjukkan bahwa sebagian besar butir pernyataan dinyatakan valid dengan nilai reliabilitas Cronbach Alpha sebesar 0,738 yang menunjukkan tingkat keandalan yang baik. Uji normalitas menggunakan Shapiro-Wilk menunjukkan nilai signifikansi 0,126 pada kelas eksperimen dan 0,776 pada kelas kontrol (p>0,05) sehingga data berdistribusi normal, sedangkan uji homogenitas menggunakan Levene Test memperoleh nilai signifikansi 0,061 (p>0,05) yang menunjukkan varians kedua kelompok homogen. Hasil uji independent sample t-test menunjukkan nilai signifikansi 0,000 < 0,05 dengan nilai t sebesar 7,406. Dengan demikian, dapat disimpulkan bahwa model pembelajaran SSCS efektif dalam meningkatkan keaktifan belajar peserta didik.